PERAN IKATAN PUSTAKAWAN INDONESIA (IPI) PROVINSI RIAU DALAM MENGEMBANGKAN KUALITAS SUMBER DAYA MANUSIA PUSTAKAWAN - Vivi Avilia; Vita Amelia; Hadira Latiar (Fihris: Jurnal Ilmu Perpustakaan dan Informasi, 2020)
The Indonesian Librarian Association (IPI) Organization of Riau Province is one of the organizations that support the quality of human resources in the librarian profession, with the existence of a professional librarians organization can help librarians in improving library management to the maximum. This study aims to determine how the Role of the Indonesian Librarian Association (IPI) of Riau Province in Developing the Quality of Librarian Human Resources. The method used in this research is descriptive qualitative research method. This research was conducted by interviewing the management and members of the Riau Province Indonesian Librarian Association (IPI) based on three indicators, namely (1) Scientific Activities, (2) Education and Training, and (3) Riau Smart Program. The results of the interviews show that of the three work program indicators, the Indonesian Librarian Association (IPI) of Riau Province has not carried out its activities properly. In the Scientific Activity Indicator, IPI of Riau Province has conducted 5 activities that lead to the development of librarians' human resources. In the Education and Training Indicator, IPI of Riau Province has conducted 1 activity that leads to the development of librarian's human resources. In the Riau Smart Program Indicator, the Provincial IPI has carried out 1 activity that leads to the development of library human resources. So it can be concluded that the role of the Indonesian Librarian Association (IPI) of Riau Province in Developing the Quality of Librarian's Human Resources has not been carried out to the maximum.Keywords: Role, Librarian, Quality, Human Resources, Indonesian Librarian Association (IPI) of Riau Province.